Wastewater COD characterization: RBCOD and SBCOD characterization analysis methods - Jingbing Zhang (Nature Portfolio, 2021)
Abstract Wastewater characterization is the basis for process design and operation optimization of wastewater treatment plants (WWTPs). In this work, a comprehensive study of the respirometry method has been performed to evaluate the biodegradable organic matters of wastewater. First, the optimal initial substrate to biomass ratio (S0/X0) was confirmed. Second, under the optimal S0/X0, the degradation curves of wastewater carbon oxygen demand (COD) components rapidly biodegradable COD (RBCOD) and slowly biodegradable COD (SBCOD) were obtained. Third, the Mann–Kendall test was performed to confirm the time point (t2) when endogenous respiration levels were reached, and the hydrolysis model was used to determine the time point (t1) of the SBCOD degradation stage. Considering the results, an adequate wastewater COD characterization method for RBCOD and SBCOD has been proposed. This study provides strong support to carry out effective and feasible process design, process diagnosis and optimization capability, can help achieve refined and stable operational management of WWTPs.